Cost-effectiveness analysis regarding postoperative administration of vitamin-d and calcium after thyroidectomy to prevent hypocalcaemia (2011)
Objective Hypocalcaemia is a frequently arising complication following total thyroidectomy. Routine postoperative prophylactic administration of vitamin D or metabolites and calcium reduce the incidence of symptomatic hypocalcaemia; this article reports evaluating its cost-effectiveness in Colombia.Methods Meta-analysis was used for comparing the administration of vitamin D or metabolites to oral calcium or no treatment at all in patients following total thyroidectomy and a cost-effectiveness analysis was designed based on a decision-tree model with local costs.Results The OR value for the comparison between calcitriol and calcium compared to no treatment and to exclusive calcium treatment groups was 0.32 (0.13-0.79 95 %CI) and 0.31 (0.14-0.70 95 %CI), respectively. The most cost-effective strategy was vitamin D or metabolites and calcium administration, having a US $0.05 incremental costeffectiveness ratio.Conclusion Prophylactic treatment of hypocalcaemia with vitamin D or metabolites + calcium or calcium alone is a cost-effective strategy.